Mechanistic and Therapeutic Implications of Extracellular Vesicles as a Potential Link Between Covid-19 and Cardiovascular Disease Manifestations - Pironti, Gianluigi; Andersson, Daniel C.; Lund, Lars H. (Frontiers in Cell and Developmental Biology, 2021)
Extracellular vesicles (EVs), which are cell released double layered membrane particles, have been found in every circulating body fluid, and provide a tool for conveying diverse information between cells, influencing both physiological and pathological conditions. Viruses can hijack the EVs secretory pathway to exit infected cells and use EVs endocytic routes to enter uninfected cells, suggesting that EVs and viruses can share common cell entry and biogenesis mechanisms. SARS-CoV-2 is responsible of the coronavirus disease 2019 (Covid-19), which may be accompanied by severe multi-organ manifestations. EVs may contribute to virus spreading via transfer of virus docking receptors such as CD9 and ACE2. Covid-19 is known to affect the renin angiotensin system (RAS), and could promote secretion of harmful EVs. In this scenario EVs might be linked to cardiovascular manifestations of the Covid-19 disease through unbalance in RAS. In contrast EVs derived from mesenchymal stem cells or cardiosphere derived cells, may promote cardiovascular function due to their beneficial effect on angiogenesis, fibrosis, contractility and immuno-modulation. In this article we assessed the potential impact of EVs in cardiovascular manifestations of Covid-19 and highlight potential strategies to control the extracellular signaling for future therapies.